Exploring the challenges and opportunities of using AI in the English classroom: A qualitative study - jumaniningsih, ariska prastiwi; Zainuddin, Zainuddin; Hamdani, Beny (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This research investigates the challenges and opportunities presented by the integration of artificial intelligence (AI) in English classes. Adopting a qualitative study approach, data were meticulously collected through in-depth interviews with English teachers, classroom observations, and the analysis of relevant documents. The findings reveal that AI holds significant promise for enhancing the learning experience, primarily through personalized material, automatic feedback, and enriched engagement for students. Moreover, AI tools like chatbots and translation software can aid learners in developing their reading, writing, speaking, and listening skills independently. However, the research also identified several challenges, including inadequate technological infrastructure, insufficient digital literacy among educators, and critical concerns regarding the ethics and privacy of student data. The study concludes that for AI to be successfully integrated into English classes, comprehensive training for teachers, supportive policies, and a tailored technological approach that addresses local needs are essential. Ultimately, when these challenges are strategically addressed, AI has the potential to serve as a catalyst for more effective and inclusive English learning. Keywords:Artificial intelligence, English learning, challenges, opportunities, qualitative studies, personalization of learning